Do trust in financial institution and financial literacy enhances intention to participate in stock market among Indian investors during COVID-19 pandemic? - Mohd Adil; Yogita Singh; Mohammad Subhan; Mamdouh Abdulaziz Saleh Al-Faryan; Mohd Shamim Ansari (Cogent Economics & Finance, 2023)
This research aims to investigate the significance of trust in financial institution and financial literacy in the investment decision-making of individual investors during the COVID-19 pandemic and investigates the strength of the theory of planned behavior (TPB) in this framework. This study considered a structured questionnaire to collect data from 460 individual investors of different districts in four states of India. For testing the research hypotheses, SPSS and PLS-SEM were taken into consideration. The findings enlighten that elements of TPB, i.e. attitude (ATT) and subjective norms (SNs), are significantly associated with investment intentions (INT) while perceived behavioral control (PBC) displays an insignificant association with INT. Furthermore, along with the original components of the TPB model, Trust in financial institution (TFI) and Financial Literacy (FL) were also incorporated in the model, which shows a significant affect on investors' intention to invest in the stock market. The results stated that TFI is the most significant factor that enhances investors' intention to participate in stock market during COVID-19 pandemic. The study describes that during the phase of uncertainty like COVID-19 pandemic trust is the most important factor that enhances investors' participation in the stock market. Authors suggest SEBI and other financial institutions should promote trust and trusting behavior in financial institutions as it is significant not only from the perspective of financial development but also to empower the individuals to gain from institutional services as well as to guard them, from possible negative effects (like financial frauds), which are more likely to be present outside of regulatory boundaries. This study is one of the initial attempts in the context of the Indian Stock Market to introduce TFI as a dual (both mediating and moderating) variable between the basic constructs of TPB. Further, the study also examines the importance of trust in financial institution and financial literacy in enhancing investors' intention to participate in stock market during COVID-19 pandemic.
Keywords: 330; COVID-19 pandemic; financial literacy; Indian stock market; theory of planned behavior; trust in financial institutions